PERNIKAHAN LINTAS AGAMA; KAJIAN MUQARIN MENURUT QURAISH SHIHAB DALAM TAFSIR AL-MISHBAH DAN HAMKA DALAM TAFSIR AL-AZHAR - Luthviyah Romziana (REVELATIA: Jurnal Ilmu Al-Qur'`an dan Tafsir, 2021)
Interfaith marriages are familiar in people's lives. This is due to advances in information media or telecommunications among the public, interfaith marriages are very easy to do. This is the root of the problem that will be discussed in the interpretation of al-Mishbah by Quraish Shihab and the interpretation of al-Azhar by HAMKA in al-Baqarah verse 221. This research is a literature review (library research) with the main source of al-Mishbah interpretation by Quraish Shihab and al-Azhar interpretation by HAMKA. This research used muqarin method, it's a method of comparison between the interpretation of al-Misbah and the interpretation of al-Azhar. The results of this study can be concluded that the law of interfaith marriage according to Quraish Shihab in the interpretation of al-Misbah is based on al-Baqarah verse 221, that prohibition of marriage between men or women who are Muslim and men or women who are other than Islam ( non-Muslims). The reason of those prohibition marriage is differences in faith. Meanwhile, according to HAMKA in al-Azhar's interpretation, it is forbidden to marry polytheists, both women and men, as idol worshipers because they are not kafa`ah or sekufu.